Karakteristik Cuaca Maritim untuk Keselamatan Pelayaran di Perairan Popoh, Tulungagung - Tasya Olivia Rinekso; Supriyatno Widagdo; Rudi Siap Bintoro (Universitas Hang Tuah, 2023)
Popoh Waters has a bay that contains a fishing boat port, a Fish Auction Place (TPI), and a Fishing Port (PPI). Indonesia has many cases of fishing boat accidents caused by bad weather. It is important to know maritime weather information to minimize fishing boat accidents. This study aims to identify the characteristics of wind, rainfall, sea waves in each season, identify the seasons that are dangerous for fishing boats and their effects on fishermen's catches. The results of the processing showed that Popoh waters had wind characteristics with a category that can endanger fishing boats in the East season with a top speed of 8.41 m/s. The characteristic of rainfall which had the highest rainfall was the West monsoon with the highest intensity of 87 mm. The characteristics of the waves in Popoh waters had waves that could endanger the sailing of fishing boats in the East season with the highest wave condition of 1.93 m.